Candidate genes for cross-resistance against DNA-damaging drugs - Wittig, Rainer; Neßling, Michelle; Mollenhauer, Jan; Korn, Bernhard; Lichter, Peter; Schadendorf, Dirk (Cancer research, 2002)
Drug resistance of tumor cells leads to major drawbacks in the treatment of cancer. To identify candidate genes for drug resistance, we compared the expression patterns of the drug-sensitive human malignant melanoma cell line MeWo and three derived sublines with acquired resistance to the DNA-damaging agents cisplatin, etoposide, and fotemustine. Subarray analyses confirmed 57 candidate genes recovered from a genome-wide scan for differential expression. By specifically addressing cancer genes we retrieved another set of 209 candidates. Exemplary Northern blot studies indicated qualitative concordance for 110 of 135 (81.4%) data points. Whereas the etoposide-resistant line showed constant expression patterns over a period of ∼2.5 years, the fotemustine- and cisplatin-resistant sublines exhibited considerable variability. Initially representing distinct entities, these two sublines finally converged in their expression patterns. A total of 110 genes was transiently or permanently deregulated in at least two resistant sublines. Fourteen genes displayed differential expression in all three of the sublines. We hypothesize that the variations in fotemustine and cisplatin resistance are based on progressive optimization and/or polyclonality. This, in addition to genomic alterations investigated by comparative genomic hybridization and evaluation of short-term response genes, can be used as a criterion for the selection of promising candidates. Among these are CYR61, AHCYL1, and MPP1, as well as several apoptosis-related genes, in particular STK17A and CRYAB. As MPP1 and CRYAB are also among the 14 genes differentially expressed in all three of the drug-resistant sublines, they represent the strongest candidates for resistance against DNA-damaging drugs.